Pedagogical grammar as the framework of TEFL research. Part 19. Correlation between the form of rules of linguistic and pedagogical grammars - Chernovaty, L. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2025)
The nineteenth paper in the series continues to discuss the correlation between linguistic (LG) and pedagogical (PG) grammars in the development of communicative grammar skills. This time, the author addresses the issue of the form of LG and PG rules, aiming to answer a series of questions. What is the general attitude of researchers towards using LG grammar information in the classroom? Are LG rules effective for grammar teaching in their current linguistic form? How can their efficiency be increased by changing their form, bearing in mind the psychological nature of the process of developing grammar skills?  An analysis of contemporary literature on this topic revealed a significant shift in attitude towards explicit focus on linguistic form in teaching, moving away from the zero tolerance of LG information in communicative language classrooms of the 1970s and 1980s. While maintaining strict adherence to the communicative nature of teaching and the prevalence of meaning-focused tasks in the classroom, researchers also acknowledge the importance of explicit attention to form for language acquisition. Stressing the teacherʼs role as a facilitator, the authors praise the use of pre-task modelling techniques, which positively impact learnersʼ attention to linguistic forms and facilitate second language skill development. Conversely, the author cautions against the uncritical revival of grammar-translation techniques, asserting that PGʼs primary objective is to foster studentsʼ communication abilities rather than their comprehension of LG structure. Based on this, he suggests that PG can disregard the principles of LG structure and establish its own rules, which may differ from those of LG. The author convincingly demonstrates the validity of this principle using examples  from  the  pre-zero-tolerance era and shows  the potential of types of pedagogical information such as models and algorithms as specific forms of PG rules. The author suggests a number of requirements for PG rules, promising to extend this list in his next contribution to the series.